Efek Nefroprotektif Ekstrak Etanol Jahe Merah (Zingiber officinale var. rubrum) Terhadap Gambaran Histopatologi Ginjal Tikus (Rattus norvegicus) Yang Diinduksi oleh Etilen Glikol - Anselia , Bella; Lubis , Asyrun Alkhairi; Sembiring, Novitaria Br (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: The kidney is a vital organ susceptible to damage from exposure to nephrotoxic compounds such as ethylene glycol. Red ginger (Zingiber officinale var. rubrum) is known to contain bioactive compounds with antioxidant and anti-inflammatory potential that may protect the kidney from injury. However, its effectiveness as a nephroprotective agent needs to be scientifically validated. Objective: To evaluate the nephroprotective effect of ethanol extract of red ginger against ethylene glycol–induced kidney damage in male white rats (Rattus norvegicus), Wistar strain. Methods: An experimental study using a post-test only control group design was conducted to minimize bias by ensuring equivalent baseline conditions among groups. A total of 25 rats were divided into five groups: normal control (distilled water), negative control (0.75% ethylene glycol), and three treatment groups (ethylene glycol + red ginger extract at doses of 100, 200, and 300 mg/kgBW/day). Parameters measured included serum creatinine levels and kidney histopathology. Data were analyzed using one-way ANOVA (p < 0.05) followed by LSD post hoc test. Results: Red ginger extract significantly reduced serum creatinine levels (p < 0.05), with the greatest reduction observed at a dose of 300 mg/kgBW (0.528 ± 0.082 mg/dL). Histopathological improvement of the kidney was also evident, indicated by decreased necrosis, cellular degeneration, and inflammatory cell infiltration. The kidney damage score in the treatment groups (score 1) was lower than in the negative control group (score 2). Conclusion: Ethanol extract of red ginger exhibits a nephroprotective effect against ethylene glycol–induced kidney injury, with the optimal dose being 300 mg/kgBW/day. These findings support the potential of red ginger as an alternative therapy for kidney disorders, although further studies are needed to elucidate the molecular mechanisms and conduct clinical trials.